STIGMA IN THE SCHOOL: THE PRACTICE OF THE CLASS COUNCIL - Paula Almeida de Castro (Editora da Universidade de Santa Cruz do Sul, 2011)
The stigmatization observed at the interaction between teachers and students at Class Council meetings is the thematic of this paper. In this paper are presented the results from the ethnographic investigation at a basic public school at Rio de Janeiro. The scenario of Class Council under observation and analysis produced clues for comprehension about the pedagogical practices planned by stigmatization, medical treatment and pathologizing the students and sometimes their families as a justification for their failures at school. It was possible to observe that students that do not fit the normal standards imposed by school received a mark, a stigma, starting to be recognized for these assignments. At the teachers speech was present the control that made visible that mark to everyone who lives together with them. The results of this study provide clues to rethink the situation of vulnerability and exclusion that some students are exposed in the evaluation of the class councils, due to difficulties in their educational processes. It also offers the possibility of thinking about the difference by the difference in an inclusive school effectively.